Immunological and Cytokine Profiling in Ulcerative Colitis: Focus on IL-10, IL-37, IFN-γ, and CD8+ T Cell - Ali N. Hamid; Dheeb, Israa Abdulwahid (American Journal of Biology and Natural Sciences, 2026)
Ulcerative colitis is one among the most prevalent forms of inflammatory bowel diseases. The hallmark of this condition is an abnormal immunologic response that gives rise to chronic inflammation of the colonic mucosa. The current literature on this subject will be discussed in this article, which will have a focus on reviewing and analyzing recent literature published between 2021 and 2025. Research has found that a breakdown of the epithelial barrier and change in gut microbiome result in an imbalance between the innate and adaptive immune systems due to excessive levels of inflammatory cytokines like IFN-γ and reduced levels of regulatory mediators IL-10 and IL-37. Data have also recently pointed towards the role of CD8+ T cells in perpetuating inflammation. Despite progress made by available medications such as 5-ASA, steroid therapies, biologics, and JAK inhibitors, there is a need for new approaches focusing on molecular fingerprinting and immunoadaptation due to current treatment incompliances and relapse. The future trends point towards enhancing research in the country and national registries for UC patients to design treatment courses in line with demographic- and environment-related features of Iraq.